Evaluation of Mathematics Learning Management of Junior High Schools in Singaraja City During Covid-19 Pandemic - Ariawan, I Putu Wisna; Ardana, I Made; Yudana, I Made (Budapest International Research and Critics University, 2021)
Many studies have been conducted related to the influence of COVID-19 pandemics on mathematics learning. Some studies showed a positive effect, but many also showed a negative effect. During the COVID-19 pandemic, mathematics learning management, especially in junior high schools, needs to be carried out properly so that the learning processes and outcomes are in accordance with the established standards. Therefore, it is necessary to conduct an evaluative study to find out how mathematics learning management has been carried out, especially in junior high schools in Singaraja City. This study was conducted using the CIPP evaluation model (Context, Input, Process, and product) involving 21 respondents consisting of principal, vice-principal of curriculum, and mathematics teachers. Respondents were determined using the purposive sampling technique in 4 public schools, namely SMP Negeri 1 Singaraja, SMP Negeri 2 Singaraja, SMP Negeri 3 Singaraja, and SMP Negeri 6 Singaraja. Data were collected using questionnaires and interviews. Based on the results, the context variable was positive (+), the the input variable was positive (+), the the process variable was negative (-), and the the product variable was negative (+). Thus, CIPP evaluation results based on the Glickman Quadrant (+ + - -) showed that mathematics learning management during COVID-19 pandemics in junior high schools in Singaraja City was in a quite effective category.